2016
DOI: 10.1103/physrevb.94.165443
|View full text |Cite
|
Sign up to set email alerts
|

Chiral interface states in graphene pn junctions

Abstract: We present a theoretical analysis of unidirectional interface states which form near p-n junctions in a graphene monolayer subject to a homogeneous magnetic field. The semiclassical limit of these states corresponds to trajectories propagating along the p-n interface by a combined skippingsnaking motion. Studying the two-dimensional Dirac equation with a magnetic field and an electrostatic potential step, we provide and discuss the exact and essentially analytical solution of the quantum-mechanical eigenproble… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…The factor k∆L in Equation 9 accounts for a possible path-difference between the edge states, where k is replaced by k = k F + eV /( v F β). The parameter β (0 ≤ β ≤ 1) was introduced to account for the renormalized edge state velocity compared to the Fermi velocity [50]. We have found that the second term alone (k∆L at α = 0) cannot lead to substantial bias dependence if the parameters are chosen realistically (∆L ∼20 nm and β = 1).…”
Section: Magnetoconductance Oscillations Marked In Orangementioning
confidence: 99%
“…The factor k∆L in Equation 9 accounts for a possible path-difference between the edge states, where k is replaced by k = k F + eV /( v F β). The parameter β (0 ≤ β ≤ 1) was introduced to account for the renormalized edge state velocity compared to the Fermi velocity [50]. We have found that the second term alone (k∆L at α = 0) cannot lead to substantial bias dependence if the parameters are chosen realistically (∆L ∼20 nm and β = 1).…”
Section: Magnetoconductance Oscillations Marked In Orangementioning
confidence: 99%
“…This value does not depend on graphene's Fermi velocity. Since V 0 /e B can be interpreted as the electric field E x induced by the potential step in the x-direction and 2 B ∝ 1/B, V 0 B / corresponds to the classical drift velocity of a charged particle in crossed magnetic and electric fields, cE x /B [42]. The effect of the Rashba SOI is a renormalization factor which decreases for increasing λ from 2/ √ π (for λ = 0) to 1 √ π (for λ ω c ) and thus tends to slightly reduce the velocities.…”
Section: Observablesmentioning
confidence: 99%
“…For λ = 0 the Hamiltonian (1) is block-diagonal in spin. Each block coincides with the Hamiltonian studied in [42] (up to the intrinsic SOI term and the Zeeman term, which can be easily incorporated) and we can borrow their results. The wave functions can be expressed as…”
Section: Appendix A: Perturbation Theorymentioning
confidence: 99%
“…Most of the work on electron optics in graphene pn junctions involves interfaces where the electrostatic potential (and hence the refractive index) changes abruptly [8,29,35,[66][67][68]. Recent experiments have demonstrated that such abrupt junctions can indeed be realized [13].…”
Section: Introductionmentioning
confidence: 99%